Electromyographic activity of rectus abdominis muscles during dynamic Pilates abdominal exercises. - Silva, Gabriela Bueno; Morgan, Mirele Minussi; Gomes de Carvalho, Wellington Roberto; Silva, Elisangela; de Freitas, Wagner Zeferino; da Silva, Fabiano Fernandes; de Souza, Renato Aparecido (Journal of Bodywork & Movement Therapies, 2015)
Summary Objective To assess the electrical behaviour of the upper rectus abdominis (URA) and lower rectus abdominis (LRA) by electromyography (EMG) during the following dynamic Pilates abdominal exercises: roll up , double leg stretch , coordination , crisscross and foot work . The results were compared with EMG findings of traditional abdominal exercises ( sit up and crunch ). Methods: Seventeen female subjects (with no experience of the Pilates method) were recruited. The URA and LRA were evaluated while 12 isotonic contractions were performed using the Pilates principles or traditional abdominal exercises. The data were normalised by a maximal voluntary isometric contraction. Normality was accepted, and ANOVA followed by Tukey test was used to determine data differences ( P < 0.05). Results: Pilates exercises double leg stretch , coordination , crisscross and foot work promoted greater muscle activation than traditional exercises, mainly in URA. Thus, these exercises have the potential to be prescribed for muscle strengthening programmes.